Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Pembelajaran PBL Berbantuan Aplikasi SAC pada Pembelajaran Pendidikan Pancasila di Kelas IV SD - Refita, Intan Putri; Mansurdin, Mansurdin (ARZUSIN, 2025)
This research is based on the results of observations in the field, namely the less than optimal implementation of learning carried out by educators, which has an impact on the low learning outcomes of students in class IV SDN 13 Kubu Gulai Bancah, Bukittinggi City. The purpose of this study is to describe the improvement in student learning outcomes using the Problem Based Learning (PBL) learning model assisted by the Smart Apps Creator (SAC) application in Pancasila Education learning. This research is a classroom action research (PTK) using qualitative and quantitative approaches which are carried out in two cycles. The results of the study found that the cycle I teaching module obtained an average percentage of 91.6% (very good) and in cycle II it obtained a percentage of 95.83% (very good). The implementation of the learning process of educator activities in cycle I obtained an average percentage of 82.14% (good) and in cycle II it obtained a percentage of 92.85% (very good). The learning process of student activities in cycle I obtained an average percentage of 75% (sufficient) and in cycle II it obtained a percentage of 89.28% (good). The learning outcomes of students in cycle I obtained an average of 71.65 (sufficient) and in cycle II obtained an average of 83.19 (good). It can be concluded that the Problem Based Learning model assisted by the Smart Apps Creator application can improve student learning outcomes in Pancasila Education learning in Elementary Schools.